Type A Insulin Resistance Syndrome- Novel insulin receptor gene mutation and familiar phenotypic variability - Analía V Freire; Paula Scaglia; Mirta G Gryngarten; Mariana Gutiérrez; Andrea J Arcari; Laura Suarez; María Gabriela Ballerini; Laura Valinotto; Mónica I Natale; Kenny Y Del Toro Camargo; Ignacio Bergadá; Rodolfo A Rey; et al. (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2019)
Type A Insulin Resistance Syndrome is due to heterozygous mutations in the insulin receptor (INSR) gene or its signaling pathway. We present a premenarcheal 14 year-old girl with normal BMI, severe hirsutism, acanthosis nigricans, clitoral hypertrophy, deep voice, enlarged polycystic ovaries, severe hyperinsulinemia and biochemical hyperandrogenism.  We identified a novel heterozygous missense variant in the tyrosine kinase domain of INSR (p.Leu1150Pro) and an heterozygous missense variant in SH2B adapter protein 1 involved in the insulin pathway (p.Ala663Val). Interestingly, the patients' mother and brother had the same INSR mutation although of a milder phenotype, reason why their IR went undiagnosed.  The novel heterozygous p.Leu1150Pro mutation in the INSR gene appears to be the cause of the type A insulin resistance syndrome; the SH2B1 mutation, likely to synergistically affect the insulin pathway, may contribute to explain the more severe presentation of the phenotype in the patient and the phenotypic variability of the syndrome within this family.